The future of learning and teaching in next generation learning spaces - Fraser, Kym, 1958- (Emerald, 2014)
Typically new generation learning spaces (NGLS) across the international higher education sector are being designed to support a more student-centred approach to teaching, through more active and collaborative learning opportunities, often using new technology (Keppell et al. 2012). However, the promise of NGLS appear to remain unfulfilled. This book takes a futuristic perspective on these unfulfilled promises, bringing to the fore the key elements of learning, teaching, professional development and design. The book addresses the compelling questions of the decade in an effort to help senior university managers think beyond the pedagogies of yesterday in order to maximize the use and design of physical learning spaces for the future. The book is written in four sections: 1) The future of learning spaces in Universities; 2) The future for learning and teaching in NGLS; 3) The future of professional development for teaching in NGLS; and 4) The future for design in learning environments and spaces.
Includes index.
Keywords: Education -- Teaching Methods & Materials -- General.; Education -- General.; Teaching skills & techniques.; Education.; Classroom utilization.; Education, Higher.; elektronické knihy; electronic books